EFEKTIVITAS PERMAINAN ENGKLEK TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDK KELAS II SDK ST. YOSEPH 4 NAIKOTEN - Adu, Astri; Lioba Nahak, Roswita; Amanda Naitili, Cornelia (STKIP Subang, 2026)
This research is motivated by the low mathematics learning outcomes of students on the material of place value in class II SDK St. Yoseph 4 Naikoten which shows the need for learning innovation to overcome this, using traditional engklek games that combine physical activity with educational elements, so that it is expected to be able to help students understand the concept of place value in a more concrete and fun way. This study aims to determine the effectiveness of traditional engklek games on mathematics learning outcomes on the material of place value of class II students SDK St. Yoseph 4 Naikoten. The type of research used is Pre-experimental design with one group pretest-posttest design. The population of this study was all class II students totaling 26 people, with saturated sampling sampling techniques. The research instruments were tests and documentation. The results showed that after the application of engklek games in learning place value material, there was an increase in student learning outcomes as seen from the average pretest score of 45.38 increasing to 89.23 on the posttest. The paired sample t-test yielded a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. The N-Gain calculation of 0.8063 is considered high. Therefore, learning using Engklek games is effective in improving mathematics learning outcomes in the place value topic for second-grade students at St. Yoseph 4 Naikoten Elementary School.